2016
DOI: 10.1016/j.chembiol.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Tagging and Enriching Proteins Enables Cell-Specific Proteomics

Abstract: SummaryCell-specific proteomics in multicellular systems and whole animals is a promising approach to understand the differentiated functions of cells and tissues. Here, we extend our stochastic orthogonal recoding of translation (SORT) approach for the co-translational tagging of proteomes with a cyclopropene-containing amino acid in response to diverse codons in genetically targeted cells, and create a tetrazine-biotin probe containing a cleavable linker that offers a way to enrich and identify tagged protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 64 publications
1
54
0
Order By: Relevance
“…155 In general, the cyclopropene handle has the advantage of being efficiently incorporated into proteins without suffering from isomerisation and presenting a relatively small size and fast kinetics (labelling reaction on proteins completed within 30 min). 155,156 copper-free dibenzocyclooctyne-azide cycloaddition. In comparison to strained alkenes, unstrained alkenes provide some advantages such as their small size, easy synthesis and enhanced stability towards cellular nucleophiles.…”
Section: Genetic Code Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…155 In general, the cyclopropene handle has the advantage of being efficiently incorporated into proteins without suffering from isomerisation and presenting a relatively small size and fast kinetics (labelling reaction on proteins completed within 30 min). 155,156 copper-free dibenzocyclooctyne-azide cycloaddition. In comparison to strained alkenes, unstrained alkenes provide some advantages such as their small size, easy synthesis and enhanced stability towards cellular nucleophiles.…”
Section: Genetic Code Expansionmentioning
confidence: 99%
“…The beads can be washed and enriched proteins may be detected using MS after reductive cleavage of the diazobenzene linker. 156…”
Section: Protein Profiling In Organismsmentioning
confidence: 99%
“…Methods such as stochastic orthogonal recoding of translation (SORT) [45] have been developed to introduce ncAAs into the whole proteome simultaneously. Instead of suppressing a stop codon, the genome is expanded by stochastically incorporating ncAAs in place of certain sense codons and under competition with the native amino acids [46]. Combining this with photo-crosslinkers has the potential to capture interactions throughout the whole proteome, as has been shown by the surrogate-based method, where a photo-crosslinker analog of a canonic amino acid is supplemented and incorporated residue specifically [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…OP-Puro requires an azide-based affinity handle or resin for enrichment [43]. SORT uses cyclopropene labels and tetrazine linkers in a ligation reaction reported to be 100 to 1000 times faster than the strain-promoted azide-alkyne cycloaddition [41]. BONCAT labels with either alkynes or azides, and enriches with complementary azide or alkyne reagents.…”
Section: Choosing a Cell-selective Proteomic Methodsmentioning
confidence: 99%
“…Elliott et al . have characterized the enrichment process and found that tagging at different codons leads to the enrichment of overlapping, but distinct sets of proteins [41]. The authors noted that simultaneous expression of multiple tRNAs (i.e., tRNA-Ala, -Ser and -Met) increases labeling efficiency.…”
Section: Metabolic Labeling: Trade-offs Between Sensitivity and Pertumentioning
confidence: 99%